THE INFLUENCE OF DYNAMIC GAMES AND RECREATIONAL ACTIVITIES ON CHILDREN - Andrieş Vasile; Onesim Florin (Editura Univeristatii "Stefan cel Mare" din Suceava, 2018)
Sport activities and gameplay are two of the most effective means used by teachers world-wide to accomplish educational goals. The involvement of children in dynamic sports tends to make the educational process more attractive and pleasant, creating a habit both at school and in their free time.